Developing QR Authentication and Fingerprint Record in an ATM Interface Using User-Centered Design Techniques - Chumpitaz, Diana (2019)
ATMs are widely used around the world, which leads to the development of new functionalities that need to consider usability. For this reason, the following article presents the development of graphical interfaces for ATM of BBVA Continental Bank, which follows a user-centered process design. In the first place, we gathered information about our target user. Then, we developed a prototype based on the previous information and the needs of the bank, which also took into account expert’s feedback. Finally, real users in the bank itself validated the prototypes.